The Trade-Off Between the Increased Colony Nurturing Ability and the Decreased Lifespan of Worker Bees (Apis mellifera) - Chaoxia Sun; Hongji Huang; Mei Yang; Guoshuai Ma; Xinyao Huang; Shaokang Huang; Xinle Duan; Jianghong Li (Insects, 2025)
High temperature is normally harmful to an organism. However, honey bees evolve, maintaining a relatively higher colony temperature of 34.5 °C in the long reproduction period. To determine the effect of such a higher colony temperature on adult bees and its biological significance, newly emerged bees were reared in cages at 34.5 °C and room temperature of 25.0 °C, respectively. Their survival rate, head weight, royal jelly-secreting gene expression, and morphology of the hypopharyngeal gland were investigated. Moreover, 40-day-old bees with significant differences in survival rate between the two temperature groups were subject to transcriptome and lipidome analysis. The result showed that the higher colony temperature was overall negative for the bees’ longevity. Transcriptome analysis showed that fatty acid metabolism-related items were enriched and the involved genes were upregulated in honey bees reared at 34.5 °C compared with the honey bees reared at 25.0 °C. Lipidomic analysis further validated that fatty acid metabolism, especially sphingolipid metabolism, was significantly altered. Such upregulation of fatty acid metabolism-related genes was also detected in young adult bees of 5 days old reared at 34.5 °C. These bees had heavier head weights, higher expression of royal jelly-secreting-related genes, and more developed hypopharyngeal glands. Such results showed that the colony temperature of 34.5 °C could accelerate the development process of newly emerged bees to be nurse bees, significantly increasing the colony nurturing capability, which in turn increased the development speed, size, and survivability of the colony. Thereby, the colony temperature of 34.5 °C shortened the lifespan of individual bees, but obtained huge returns at the colony level, with remarkable biological significance.